Key points of technical review for the registration of SARS-CoV-2 nucleic acid tests in China - An, J. (Future Medicine Ltd., 2021)
In response to the outbreak of COVID-19, in accordance with the principles of â€ unified command, early involvement, prompt review and scientific approval' as well as the requirements of ensuring product safety, effectiveness and controllable quality, the Center for Medical Device Evaluation (CMDE) has issued Key Points of Technical Review for the Registration of SARS-CoV-2 Nucleic Acid Tests (Key Points) to provide the requirements of tests. Because of the sustainability of the pandemic, more efforts and attempts are needed for SARS-CoV-2 detection and control. This article interprets the Key Points issued by the CMDE and provides certain refinements to wider audiences. © 2021 Newlands Press.